1999
DOI: 10.1002/jor.1100170114
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent pneumatic compression of legs increases microcirculation in distant skeletal muscle

Abstract: Intermittent pneumatic compression has been established as a method of clinically preventing deep vein thrombosis, but the mechanism has not been documented. This study observed the effects of intermittent pneumatic compression of legs on the microcirculation of distant skeletal muscle. The cremaster muscles of 80 male rats were exposed, a specially designed intermittent pneumatic-compression device was applied to both legs for 60 minutes, and the microcirculation of the muscles was assessed by measurement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
26
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 26 publications
2
26
1
Order By: Relevance
“…Our cell culture results are consistent with previous studies in animal models (26), which showed that pneumatic compression causes vasodilation in arteries and veins. In those experiments, vasodilation reached maximum levels 30 min after initiation of compression and could be completely blocked by an inhibitor of NOS.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our cell culture results are consistent with previous studies in animal models (26), which showed that pneumatic compression causes vasodilation in arteries and veins. In those experiments, vasodilation reached maximum levels 30 min after initiation of compression and could be completely blocked by an inhibitor of NOS.…”
Section: Discussionsupporting
confidence: 93%
“…This result suggests that inhibition of the tissue factor pathway, the major physiological initiating mechanism of blood coagulation, might be an important mechanism for the antithrombotic effect of EPC. 3) Recently, Liu et al (26) showed in an animal model that there is significant vasodilation in arterial and venous vessels during the application of EPC and further demonstrated that the vasodilation could be completely blocked by nitric oxide synthase (NOS) inhibitor. They also found that the inflation rate is a dominant factor in determining the degree of vasodilation by EPC (27).…”
mentioning
confidence: 99%
“…The reason for the discrepancy between these two studies (18,25) is not readily apparent, because the method used to assess changes in leg blood flow was identical. Another previous study comprising 14 healthy subjects reported the effects of leg compression by bandaging on leg pulsatile blood flow using a nuclear MR flowmeter (18,19). A flow increase of 29% was reported for a pressure increase of ϳ40 mmHg.…”
Section: Discussionmentioning
confidence: 97%
“…An effect on arterial flow is indicated by a study on volunteers in whom, during foot-to-knee compression bandaging, an increase of lower leg pulsatile blood flow was observed by nuclear magnetic resonance (MR) flowmetry (22,23). Intermittent pneumatic foot and calf compression is also an effective therapeutic means to reduce the symptoms of venous insufficiency (4,17,19,26). Using color flow duplex imaging of the popliteal artery, Labropoulos et al (17) found increased blood flow in healthy volunteers during intermittent pneumatic foot and calf compression.…”
mentioning
confidence: 99%
“…The search for the biological basis of the beneficial effects of IPC application through the use of animal models (25,46) requires that the protocols used and, most importantly, the effects evoked by the compressions mimic the ones obtained in the clinical scenario. Accordingly, the protocol employed in the present investigation was based on the most commonly used stimulation characteristics utilized for treatment of patients with PAD, i.e., 120 mmHg, with cycles of 4 s of inflation and 16 s of deflation and a minimum time of exposure of 150 min (13,47).…”
Section: Discussionmentioning
confidence: 99%